ANALISIS FAKTOR VIRALITAS KONTEN BERITA PADA TIKTOK DAN INSTAGRAM: STUDI KASUS PADA AKUN MEDIA KUPASSOS - Lismiati Fauziah; Ahmad Hendy Prasetyo; Feriyanto; Hilma Nurullina Fitriani; Opik Jamaludin (Jurnal Komunikasi, 2026)
This study aims to analyze the factors influencing the virality of news content on TikTok and Instagram, using a case study of the KUPASSOS Media account. The method used in this study is a descriptive qualitative approach, with data collection techniques through content observation, documentation, and literature review. The research object is news content published on the Instagram (@kupassos) and TikTok (@kupassosial) accounts, with a focus on the level of engagement and characteristics of the resulting content. The results show that the virality of news content is influenced by several key factors, namely the characteristics of engaging, concise, and trend-relevant content, as well as high user engagement, including likes, comments, shares, and views. Furthermore, social media algorithms play a crucial role in distributing content to a wider audience, especially when the content receives a positive initial response. Audience psychological factors such as fear of missing out (FOMO) and the need for social validation also contribute to increased engagement with viral content. Thus, the virality of news content is the result of the interaction between content quality, user engagement, and the platform's algorithmic system, all working simultaneously to expand the reach of information on social media.